Institutional Problems of Regional Development in Russia - Syssoeva, Natalia (Quaestiones Geographicae, 2010)
The paper presents problems of spatial policy in Russia related to the formation of institutional conditions for regional development. Development institutions are characterised in terms of three functional groups. Distributive institutions reallocate funds between regions and they are the main subject of research on development factors. Problems of the redistribution sphere include losses of regions and municipalities in rental payments and household incomes. Transformational institutions contribute to the transformation of income into investment, and their effectiveness depends upon the quality of human capital and forms of relationships in local and regional communities. Organising institutions are usually formed by the state to arrange and stimulate the implementation of measures determined by the state regional development policy. The programme of economic and social development of Siberia is analysed as an example of institutional framework construction. The role of informal norms in institutional environment development is stressed.